Using of the ROSA method to assess the musculoskeletal load on computer workstations - Zbigniew Jóźwiak; Teresa Makowiec Dąbrowska; Elżbieta Gadzicka; Jadwiga Siedlecka; Agata Szyjkowska; Marcin Kosobudzki; Piotr Viebig; Alicja Bortkiewicz (Nofer Institute of Occupational Medicine, 2019)
Background The aim of the study was to compare the musculoskeletal system load assessed using the rapid office strain assessment (ROSA) and rapid upper limb assessment (RULA) methods in computer operators, and to determine the correlation of the obtained results with the occurrence and intensity of musculoskeletal complaints (MSCs) in these individuals. Material and Methods In a group of 72 persons (38 women and 34 men) working with a computer for > 4 h/day, the ROSA and RULA methods were used to assess the load, while a questionnaire modeled on the Standardized Nordic Questionnary was used to assess the frequency and severity of MSCs. Results Musculoskeletal complaints occurred in about 66% of the investigated women and 62% of the investigated men within the previous year. The results of the ROSA and RULA methods were not convergent. The final result of the ROSA method (scale 1−10 pts) was 2−6 pts (M = 3.51±1.09), while the final result of the RULA method (scale 1−7 pts) ranged 2−4 pts (3.00±0.17). The values of partial and final scores in the ROSA method were correlated with the number of concurrent ailments and intensity of complaints in various regions of the musculoskeletal system. The assessment of the position of particular parts of the body during work, performed using the RULA method, in people with or without MSCs was almost identical. Conclusions The use of the ROSA method has shown that it is a useful and easy-to-use tool for assessing computer workstations and can be successfully disseminated. Med Pr. 2019;70(6):675-99